2021
DOI: 10.1002/aic.17429
|View full text |Cite
|
Sign up to set email alerts
|

A decoupling strategy for protecting sensitive process information in cooperative optimization of power flow

Abstract: Optimal power flow (OPF) with close cooperation between the power grid and flexible electricity‐intensive chemical processes can reduce costs for the grid and for electricity users. However, this would require sharing detailed chemical process models, which may reveal confidential information and potentially jeopardize competitive advantages for a chemical process operator. We propose an algorithm that enables economically advantageous cooperation without the need to exchange sensitive information. Low‐order l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Some previous work has addressed this problem with decoupling strategies to protect proprietary information while still optimizing power flow between participating loads and the grid. 64 Recent publications have shown that the cooperation and cooperation between industrial facilities can improve overall grid operations even when using decoupling strategies to protect advantages. 65,66 Some industrial load profile benchmarking has been done by the Electric Power Research Institute with their Load Shape Library.…”
Section: Data Sharing Cooperation and Benchmarkingmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous work has addressed this problem with decoupling strategies to protect proprietary information while still optimizing power flow between participating loads and the grid. 64 Recent publications have shown that the cooperation and cooperation between industrial facilities can improve overall grid operations even when using decoupling strategies to protect advantages. 65,66 Some industrial load profile benchmarking has been done by the Electric Power Research Institute with their Load Shape Library.…”
Section: Data Sharing Cooperation and Benchmarkingmentioning
confidence: 99%
“…Information concerning production and process energy use has typically been kept private, as this information could give certain plants a competitive advantage over other facilities. Some previous work has addressed this problem with decoupling strategies to protect proprietary information while still optimizing power flow between participating loads and the grid 64 . Recent publications have shown that the cooperation and cooperation between industrial facilities can improve overall grid operations even when using decoupling strategies to protect advantages 65,66 …”
Section: Five Improvement Areasmentioning
confidence: 99%